Strategies for peasant life in four communities located in protected areas: An economic worldview beyond agriculture (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2016)
In this study the types of livelihood strategies that put forward four rural communities located in protected areas Chocoyero-El Brujo and Miraflor- Moropotente are analyzed. For the study surveys that allowed specific information on the way how they are configured and adapted to the varying conditions of life environment these strategies were applied. 63% of rural households live from agriculture and the remaining 37% in addition to agriculture of other nonagricultural economic activities that are complementary living. So the social reproduction of the UDC, is not exclusively in the context of agriculture, but also other accompanying activities. The interpretive frameworks that theoretically discuss the findings is the new rurality, and theoretical lectures on the life strategies. The peasant culture is not synonymous with agriculture, there are components of rural culture which are broader and determine specific patterns of behavior, their links with urban influence decisively in the adoption of other livelihood strategies that are not proper the rural context.REICE Vol.3(6) 2015: 55-76
Keywords: Livelihoods; productive culture; pluriactivity; peasant household; protected area